Building a Model of Work Force Reduction that is Grounded in Pertinent Theory and Data: Reply to Mckinley - Sutton, Robert I.; D’Aunno, Thomas (Academy of Management Review, 1992)
Robert I. Sutton, Thomas D'Aunno, Building a Model of Work Force Reduction That is Grounded in Pertinent Theory and Data: Reply to McKinley, The Academy of Management Review, Vol. 17, No. 1 (Jan., 1992), pp. 124-137